2006
DOI: 10.1002/jnr.20982
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of the chemokine CXCL10 reduces apoptosis and increases axon sprouting after spinal cord injury

Abstract: Spinal cord injury (SCI) is followed by a secondary degenerative process that includes cell death. We have previously demonstrated that the chemokine CXCL10 is up-regulated following SCI and plays a critical role in T-lymphocyte recruitment to sites of injury and inhibition of angiogenesis; antibody-mediated functional blockade of CXCL10 reduced inflammation while enhancing angiogenesis. We hypothesized, based on these findings, that the injury environment established by anti-CXCL10 antibody treatment would su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 66 publications
6
59
0
2
Order By: Relevance
“…The inflammatory response is a major component of secondary degeneration that follows the acute stages of SCI (Hausmann, 2003). Several studies support the notion that the inflammatory response is detrimental following injury, causing further loss of tissue that was spared by the initial mechanical insult (Glaser et al, 2004;Glaser et al, 2006;Gonzalez et al, 2003;Popovich et al, 1997;Popovich et al, 1999;Popovich et al, 2002;Taoka et al, 1997). This age-associated loss in neuroprotection and regulation of inflammation may drive the ageassociated increases in pathology and demyelination that we observed.…”
Section: Age-associated Deficitssupporting
confidence: 81%
“…The inflammatory response is a major component of secondary degeneration that follows the acute stages of SCI (Hausmann, 2003). Several studies support the notion that the inflammatory response is detrimental following injury, causing further loss of tissue that was spared by the initial mechanical insult (Glaser et al, 2004;Glaser et al, 2006;Gonzalez et al, 2003;Popovich et al, 1997;Popovich et al, 1999;Popovich et al, 2002;Taoka et al, 1997). This age-associated loss in neuroprotection and regulation of inflammation may drive the ageassociated increases in pathology and demyelination that we observed.…”
Section: Age-associated Deficitssupporting
confidence: 81%
“…Accordingly, several studies have shown that therapies targeting various factors involved in the secondary degeneration cascade lead to tissue sparing and improved behavioral outcomes in spinal cord-injured animals (Bao et al, 2003;Cuzzocrea et al, 2006;Glaser et al, 2006). Much of the damage that occurs in the spinal cord following traumatic injury is due to the secondary effects of glutamate excitotoxicity, Ca 2ϩ overload, and oxidative stress, three mechanisms that take part in a spiraling interactive cascade ending in neuronal dysfunction and death (Anderson and Hall, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several studies have shown that therapies targeting various factors involved in the secondary degeneration cascade lead to tissue sparing and improved behavioral outcomes in spinal cord-injured animals (Bao et al, 2003;Cuzzocrea et al, 2006;Genovese et al, 2006b;Glaser et al, 2006). Much of the damage that occurs in the spinal cord after traumatic injury is due to the secondary effects of glutamate excitotoxicity, Ca 2ϩ overload, and oxidative stress, three mechanisms that take part in a spiraling interactive cascade ending in neuronal dysfunction and death (Tator, 1991;Anderson and Hall, 1993).…”
Section: Discussionmentioning
confidence: 99%